Comparison of Serum Calcium Level Among Patients with Different Stages of Hypoxic Ischaemic Encephalopathy Due to Perinatal Asphyxia - Mst Rukshana Begum Chowdhury; Sifat Binte Karim; Md Mostafa Zaman; Shanjeeda Shormin; Md Sariful Islam; Nusrat Nuren (Journal of Rangpur Medical College, 2026)
Background: Perinatal asphyxia is a leading cause of neonatal hospital admission, particularly in low- and middle-income countries. It causes diminished oxygen supply to brain resulting hypoxic ischaemic encephalopathy with three distinct stages. Higher HIE grades have been associated with reduced calcium levels. This emergency condition can lead to multi-organ dysfunction and can affect the neonatal calcium profile causing mainly hypocalcemia. Objective: To compare the serum calcium level among different stages of Hypoxic ischaemic encephalopathy (HIE) in perinatal asphyxia Methods: This cross-sectional observational study was conducted in department of Paediatrics, Rangpur medical college hospital on 212 neonates with perinatal asphyxia with different stages of HIE. Results: Among 212 neonates birth asphyxia was predominant in male (56.5%). Birth asphyxia was predominant in vaginal delivery (64%). Majority of the neonates were in HIE stage II (58.5%) followed by stage III (21.7%) and stage I (19.8%). Serum calcium level was significantly lower in stage III to stage-II HIE (5.1±1.66 vs 6.1±1.1.54, p-value=0.0003) and stage II to stage-I (6.1±1.1.54 vs 7.2±1.35, p-value=.0003). Conclusion: Serum calcium level tends to decrease in asphyxiated neonate which is most subjacent in HIE stage III. J Rang Med Col.2026 Mar;11(1): 69-72